Мішана задача для одного нелінійного псевдопараболічного рівняння - Доманська, Г.П. (Видавничий дім "Академперіодика" НАН України, 2008)
Some sufficient conditions for the existence of a local generalized solution of the initial boundary-value problem for a nonlinear pseudoparabolic equation are obtained. Some conditions for the non-existence of a global solution are obtained too.